Pengaruh Terapi Relaksasi Otot Progresif terhadap Respon Fisiologis Pasien Hipertensi - Ni Luh Putu Ekarini; Heryati Heryati; Raden Siti Maryam (Politeknik Kesehatan Tanjung Karang, 2019)
Hypertension is one type of non-communicable disease, which is increasing every year. Hypertension is a condition where systolic blood pressure ≥140 mmHg and/ or diastolic blood pressure ≥90 mmHg. Today the treatment of disease including hypertension has been widely modified between pharmacological therapy and non-pharmacological therapy. One of the non-pharmacological therapies currently used is relaxation therapy in a deep breath and progressive muscle relaxation. This study was to determine the effect of progressive muscle relaxation therapy on the physiological response of hypertensive patients at Cipayung Health Center, East Jakarta. The research design used was a quasi-experimental pre-test post-test with control group design. The number of research samples was 37 respondents in the intervention group and 37 respondents for the control group. The results showed that there was a difference in diastolic blood pressure between the intervention group and the control group after progressive muscle relaxation intervention (p-value=0,000).